2016
DOI: 10.1007/s10863-016-9659-7
|View full text |Cite
|
Sign up to set email alerts
|

MiR-221 promotes IgE-mediated activation of mast cells degranulation by PI3K/Akt/PLCγ/Ca2+ pathway

Abstract: Mast cells play a pivotal role in the immediate reaction in asthma. In a previous study, it was found that MicroRNA-221 (miR-221) was associated with asthma. Hence, in the present study, the role and the potential mechanisms of miR-221 on immunoglobulin E (IgE)-mediated activation of mast cells degranulation were investigated. MiR-221 expression was first quantified by qRT-PCR in IgE-mediated activation of mast cells. RBL-2H3 cells were then transfected with miR-221 mimic or miR-221 inhibitor, the IgE-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…In addition, IL-8 expression has been shown to be regulated by the PI3K/AKT signaling pathway [65]. The PI3K/AKT signaling pathway also plays a key role in the IgE-mediated maturation and activation of mast cells [66,67]. The suppression of the PI3K/AKT signaling pathway has been reported to lead to the inhibition of TNF-α-induced inflammation [68].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-8 expression has been shown to be regulated by the PI3K/AKT signaling pathway [65]. The PI3K/AKT signaling pathway also plays a key role in the IgE-mediated maturation and activation of mast cells [66,67]. The suppression of the PI3K/AKT signaling pathway has been reported to lead to the inhibition of TNF-α-induced inflammation [68].…”
Section: Discussionmentioning
confidence: 99%
“…In sensitized subjects, mast cells are sensitized by binding IgE antibodies. Re‐exposure to specific antigens can activate sensitized mast cells to elicit release of allergic mediators . This study showed that re‐exposure to the specific antigen OVA and levels of serum histamine, the marker of mast cell activation, were significantly increased.…”
Section: Discussionmentioning
confidence: 74%
“…Immunoglobulin (Ig) E is the major mediator in allergic responses. IgE binds the high‐affinity receptor, FcɛRI, on the surface of mast cells to sensitize them . The sensitized mast cells are activated upon re‐exposure to specific antigens to release chemical mediators that trigger allergic responses .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations